2012
DOI: 10.1111/j.1365-2400.2011.00841.x
|View full text |Cite
|
Sign up to set email alerts
|

Are introduced gibel carp Carassius gibelio in Turkey more invasive in artificial than in natural waters?

Abstract: The underlying mechanisms responsible for ecological plasticity and consequent invasive character of non‐native freshwater fish species, variations in growth and life history traits in gibel carp Carassius gibelio (Bloch) were compared in natural and artificial water bodies of Turkey. Females significantly outnumbered males in all natural and most artificial waters. Discriminate function analysis differentiated gibel populations into three separate groups (natural lakes, artificial water bodies and running wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
54
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 47 publications
1
54
1
Order By: Relevance
“…Smaller size at maturity was higher in populations from artificial waterbodies than those inhabiting running waters. Length and age at maturity, fecundity, and GSI are not generally factors in relative condition and oocyte size (Tarkan et al, 2012).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Smaller size at maturity was higher in populations from artificial waterbodies than those inhabiting running waters. Length and age at maturity, fecundity, and GSI are not generally factors in relative condition and oocyte size (Tarkan et al, 2012).…”
Section: Discussionmentioning
confidence: 92%
“…The difference between male and female GSI suggests that the energy invested in gamete production by males is probably less than that invested by females (Hacker, 1979). GSI and smaller size at maturity would indicate populations that show more opportunistic life history traits than others (Tarkan et al, 2012). Lengths at maturity were 12.8 cm for A. mossulensis and 11.4 cm for A. marmid.…”
Section: Discussionmentioning
confidence: 98%
“…The rapid expansion and high abundance of Prussian carp in Turkey and also in some parts of Europe makes it problematic (Özcan, 2007;Gaygusuz et al, 2007;Lusková et al, 2010;Liasko et al, 2011;Tarkan et al, 2012). Recent studies have focused on the possible negative impact of this species to distribution (Özcan, 2007), abundance (Gaygusuz et al, 2007;Perdikaris et al, 2012), reproduction (Aydın et al, 2011) and some growth parameters (Leonardos et al, 2008;Tarkan et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The initial introduction and spread of A. woodiana is thought to have occurred via the export of fish species such as Carassius auratus, C. gibelio, Ctenopharyngodon idella, and Hypophthalmichthys molitrix from eastern Asia for ornamental or biological control purposes (Watters, 1997). Carassius species in particular have spread extensively in Turkish waters (Tarkan et al, 2012) and C. gibelio is known to occur in Lake Sapanca (A.S. Tarkan, unpublished data), and is also distributed throughout the country, raising the possibility that A. woodiana may be more widespread in the region than this single case might suggest. A recent study on the invasion success of A. woodiana demonstrated that it is a successful invasive species tolerant of a wide range of environmental conditions (Douda et al, 2012).…”
Section: Discussionmentioning
confidence: 99%